1978
DOI: 10.1139/m78-023
|View full text |Cite
|
Sign up to set email alerts
|

The lipopolysaccharide (R type) as a common antigen of Neisseria gonorrhoeae. II. Use of hen antiserum to gonococcal lipopolysaccharide in a rapid slide test for the identification of N. gonorrhoeae from primary isolates and secondary cultures

Abstract: An antiserum has been prepared in hens to R-type gonococcal lipopolysaccharide (LPS) and used in a simple slide-agglutination test for the identification of Neisseria gonorrhoeae. Anti-LPS serum agglutinated gonococcal cells representative of the four colony types of N. gonorrhoeae. Absorption of the antiserum with LPS removed the agglutinating activity. Secondary cultures (1120) were tested without observation of the colony type and all were agglutinated. No agglutination occurred with strains of Neisseria me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1979
1979
1998
1998

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…In this respect, the effects of any variations in the structure of the gonococcal lipopolysaccharide may have a particularly important role in determining the physicochemical nature of the gonococcal surface. It has been shown that T1 variants may contain S type lipopolysaccharide (21), in addition to R type lipopolysaccharide (22,28), the only type found in T4 variants. Furthermore, T1 variants have a larger amount of acidic glycoses, N-acetylneuraminic acid and 2-ketodeoxyoctulosonic acid than T4 variants (30).…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, the effects of any variations in the structure of the gonococcal lipopolysaccharide may have a particularly important role in determining the physicochemical nature of the gonococcal surface. It has been shown that T1 variants may contain S type lipopolysaccharide (21), in addition to R type lipopolysaccharide (22,28), the only type found in T4 variants. Furthermore, T1 variants have a larger amount of acidic glycoses, N-acetylneuraminic acid and 2-ketodeoxyoctulosonic acid than T4 variants (30).…”
Section: Resultsmentioning
confidence: 99%
“…To determine if the H8 epitope was exposed on viable gonococci, slide agglutination assays were performed as described (20). Colonies from 18-h cultures, grown on clear-typing medium, were used.…”
Section: Slide Agglutinationmentioning
confidence: 99%
“…The specific protection of chicken embryos from hens immunised with formalin-killed group A meningococci (Diena et al, 1976(Diena et al, , 1978 suggested that the hen-embryo model might be useful for characterising the immunogenic properties of purified meningococcal antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the R-type LPS of N. gonorrhoeae is immunogenic in hens and that embryos obtained from immunised hens are protected against challenge with homologous and heterologous strains of N. gonorrhoeae (Diena et al, 1978a and b;Wallace et al, 1978). SP-2 contained c 10% of LPS and antibodies to common LPS determinants might be responsible for the protection.…”
Section: Discussionmentioning
confidence: 99%